Are new digital influencers ruining your business?: The effects of negative word-of-mouth initiated by social media new influencers in fashion on consumers´ intentions to purchase and recommend the brand - Langaro, D.; Loureiro, S. M. C.; Paula, A. B. (2019 Global Fashion Management Conference at Paris Proceedings, 2019)
The rise of social media new influencers (e.g. bloggers, instagrammers and youtubers) has imprinted major impact in marketing communication strategies, with companies realizing the potential of fostering relationships with these new digital influencers (Acar & Polonsky, 2007). The rationale behind doing marketing with influencers lays on reaching their audiences, while leveraging on influencers ́ credibility, referent and expert power for communicating brand messages (Tuten & Solomon, 2017). While communicating with their audiences, the new influencers tend to share brand related messages. Among them are product reviews which are propagated by means of electronic word-of-mouth (e-WOM) using media resources like Instagram posts, Instagram stories or YouTube vlogs.